Business Data Communications and Networking - FitzGerald, Jerry, 1936-; Dennis, Alan; Durcikova, Alexandra (Hoboken, NJ : Wiley, 2021)
"This chapter introduces the basic concepts of data communications. It describes why it is important to study data communications, how data communications fit within the discipline of Management Information Systems (MIS), and introduces you to the three fundamental questions that this book answers. Next, it discusses the basic types and components of a data communications network. Also, it examines the importance of a network model based on layers. Finally, it describes the three key trends in the future of networking"--
Introduction to data communications -- Application layer -- Physical layer -- Data link layer -- Network and transport layers -- Network design -- Wired and wireless local area networks -- Backbone networks -- Wide area networks -- The internet -- Network security -- Network management.
Includes index.
Keywords: Data transmission systems; Computer networks; Office practice -- Automation